2017
DOI: 10.1111/btp.12511
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional ant diversity along a secondary successional gradient in a tropical forest

Abstract: The taxonomic diversity (TD) of tropical flora and fauna tends to increase during secondary succession. This increase may be accompanied by changes in functional diversity (FD), although the relationship between TD and FD is not well understood. To explore this relationship, we examined the correlations between the TD and FD of ants and forest age in secondary forests at the α‐ and β‐diversity levels using single‐ and multi‐trait‐based approaches. Our objectives were to understand ant diversity patterns and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
2
14
4
1
Order By: Relevance
“…We found that ant species richness was remarkably constant across the chronosequence, conveying a high resistance to disturbance. However, ant richness has been reported to have idiosyncratic responses to chronosequences in the majority of studies, as some report an increase of species richness or diversity with regeneration time (Bihn et al, 2008; Rocha‐Ortega et al, 2018), while others found no such relationship (Belshaw & Bolton, 1993; Estrada & Fernández, 1999; Hethcoat et al, 2019; Schmidt et al, 2013; Staab et al, 2014). Ultimately, species richness changes depend on the species pool that is specialized to disturbed areas, which replace forest species during disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ant species richness was remarkably constant across the chronosequence, conveying a high resistance to disturbance. However, ant richness has been reported to have idiosyncratic responses to chronosequences in the majority of studies, as some report an increase of species richness or diversity with regeneration time (Bihn et al, 2008; Rocha‐Ortega et al, 2018), while others found no such relationship (Belshaw & Bolton, 1993; Estrada & Fernández, 1999; Hethcoat et al, 2019; Schmidt et al, 2013; Staab et al, 2014). Ultimately, species richness changes depend on the species pool that is specialized to disturbed areas, which replace forest species during disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ants are sensitive to environmental variables and respond rapidly to anthropogenic changes (Del Toro, Ribbons, & Pelini, 2012). For instance, taxonomic and functional diversity of ants are lost during initial stages of secondary succession (Bihn, Verhaagh, Brändle, & Brandl, 2008; Rocha-Ortega et al., 2017) due to soil and vegetation condition changes (Schmidt, Ribas, & Schoereder, 2013). Given this context, ants are useful for testing hypotheses about secondary succession via the studying of nesting resource diversity changes (Murnen, Gonthier, & Philpott, 2013) and microhabitat conditions (Schmidt et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, species diversity of beetles declined (Manrique-Ascencio, 2010), while that of trees (Mora et al, 2015) and bats (Avila-Cabadilla et al, 2009) increased along succession, approaching the values observed in the oldgrowth forest in less than 15 years. Similarly, in the wet site, the species diversity of most studied groups (trees, ants, amphibians, reptiles, bats and terrestrial medium-mammals) increased during the first 20 years of succession, approaching the values observed in the old-growth forest (de la Peña-Cuéllar et al, 2012;Rocha-Ortega et al, 2018;van Breugel et al, 2006). The rapid recovery of secondary tropical forests has led to the hypothesis that low habitat differentiation may allow for the conservation of rich animal communities in landscapes (Boege et al, 2019;Suazo-Ortuño et al, 2015b).…”
Section: Recovery Of Biodiversity and Ecosystem Processes Along Secon...mentioning
confidence: 91%